2017
DOI: 10.1159/000485947
|View full text |Cite
|
Sign up to set email alerts
|

Glaucocalyxin B Alleviates Lipopolysaccharide-Induced Parkinson’s Disease by Inhibiting TLR/NF-κB and Activating Nrf2/HO-1 Pathway

Abstract: Background/Aims: Parkinson’s disease (PD) is a common neurodegenerative disease in the old population, characterized by dopaminergic neuron loss, inflammation and oxidative stress injury in the substantia nigra. Glaucocalyxin B (GLB), an ent-kauranoid diterpenoid isolated from Rabdosia japonica, has anti-inflammation and anti-tumor effects. However, its effects on PD remain unclear. Methods: PD was introduced in rats via injection of lipopolysaccharide (LPS) into cerebral corpus striatum, and GLB was given int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…17 SOD is a key factor for the defense against tissue damages induced by ROS. 19 These results suggest that GLB could attenuate cerebral I/R injury through inhibiting oxidative stress. 19 These results suggest that GLB could attenuate cerebral I/R injury through inhibiting oxidative stress.…”
Section: Discussionmentioning
confidence: 82%
“…17 SOD is a key factor for the defense against tissue damages induced by ROS. 19 These results suggest that GLB could attenuate cerebral I/R injury through inhibiting oxidative stress. 19 These results suggest that GLB could attenuate cerebral I/R injury through inhibiting oxidative stress.…”
Section: Discussionmentioning
confidence: 82%
“…The immunohistochemistry revealed higher expressions of kidney injury molecule 1 (Kim‐1), nuclear factor‐κB (NF‐κB), nuclear factor erythroid 2‐related factor 2 (Nrf2) and cardiac troponin I (CTnI) in NaF only treated rats. The NF‐κB and Nrf2 are both transcription factors that regulate a number of genes responsible for oxidative stress, inflammation, and antioxidants . From the results we obtained, NaF toxicity upregulated both NF‐κB and Nrf2 indicating the capacity of NaF to modulate signaling associated with inflammation, oxidative stress and antioxidant response elements (ARE).…”
Section: Discussionmentioning
confidence: 88%
“…3). Recent findings based on animal models studies have shown the neuroprotective effects of many compounds, such as the triterpene Ginsenoside Rb1 [95] and the alkaloid Glaucocalyxin B [96] as well as endogenous metabolites like alpha-lipoic acid [97] and estradiol [98], all involved in the activation of the Nrf2/ARE signaling. Aging is the main risk factor for neurodegeneration and is associated with enhanced ROS/RNS levels and lower antioxidant capacity.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%